Early development conditions and the oxidative cost of social context in adulthood: an experimental study in birds - Romero-Haro, Ana A.; Canelo, Tara; Alonso-Alvarez, Carlos (Frontiers in Ecology and Evolution, 2015)
Environmental conditions during early life may shape phenotype in adulthood. Early adverse conditions may increase the oxidative stress in adults, which could affect their reproductive output and survival. It has also been hypothesized that the larger the reproductive investment, the higher the oxidative stress. We tested this and the potential influence of early oxidative stress on how individuals respond to a reproductive stimulation. The synthesis of the antioxidant glutathione was inhibited in captive zebra finches (Taeniopygia guttata) during growth. In adulthood, the expression of a carotenoid-based sexual signal, bill redness, increased in both sexes, with females also being heavier than controls. The social context of control and glutathione-inhibited males was then manipulated to stimulate precopulatory reproductive investments. Males were individually caged in front of a female or another male. We predicted that males enduring lower early antioxidant levels and placed close to a female should pay the highest cost of a hypothetical increase in bill redness in terms of oxidative damage. However, early conditions only influenced the male’s phenotype via their partners. Males caged with females showed increases in circulating pigment (carotenoid) levels, but only when females endured early low antioxidant values. This was probably related to the higher attractiveness of these females. Nevertheless, the bill redness of males did not differ during the social manipulation. Moreover, males facing females from any early condition group showed lower oxidative damage levels in plasma lipids. This result agrees with some findings in rodents, also in captivity. However, the effect may be due to increased triglyceride levels and body mass in males not facing females, as variation in these traits explained oxidative damage variability. The importance of considering housing conditions and life history when interpreting oxidative stress-related trade-offs is highlighted.